Peningkatan Hasil Belajar IPA melalui Pembelajaran CTL Berbantu Media Audiovisual pada Siswa Kelas IV SD Negeri Karangbandung 02 - Kusumahati, Meidian (Universitas Sebelas Maret, 2020)
The purpose of this Classroom Action Research is to improve learning outcomes of science lessons on the theme Caring for living things in fourth grade students of SD Negeri Karangbandung 02, Keanggungan District, Brebes Regency using the CTL model assisted by audiovisual media. In this model, classroom action research is carried out through four stages, namely planning, action implementation, observation, and reflection and is carried out in three cycles. From this classroom action research, the results obtained in the first cycle that the average student score was 70.13 with a completeness percentage of 54.17%. In the second cycle it increased to 79.15 with a completeness percentage of 65.7%. In the third cycle the average score of students became 87.08 with a completeness percentage of 91.6%. Based on the data obtained, it can be concluded that the use of the CTL model with the aid of audiovisual media can improve the learning outcomes of the science theme Caring for Living Creatures in fourth grade students of SD Negeri Karangbandung 02 Ketanggungan District, Brebes Regency